Effects of alpha lipoic acid, ascorbic acid-6-palmitate, and fish oil on the glutathione, malonaldehyde, and fatty acids levels in erythrocytes of streptozotocin induced diabetic male rats - Yilmaz, Ö; Özkan, Y; Yildirim, M; Öztürk, AI; Ersan, Y (Wiley, 2002)
In this research, it has been aimed to evaluate the improvement effects of alpha lipoic acid (ALA), ascorbic acid-6-palmitate (AA6P), fish oil (FO), and their combination (COM) on some biochemical properties in erythrocytes of streptozotocin (STZ)-induced diabetic male rats. According to experimental results, glutathione (GSH) level in erythrocytes decreased in diabetes (P<0.01), D + ALA, and D + AA6P groups (P<0.001). Malonaldehycle (MA) level increased in diabetes (P<0.05), D + FO, and D + COM groups (P<0.001), but its level in D + AA6P and D + ALA groups was lower in diabetes group (P<0.01). Total lipid level in diabetes and diabetes plus antioxidant administered groups were higher than control. Total cholesterol level was high in diabetes and D + ALA groups (P<0.035), but its level reduced in D + FO compared to control and diabetes groups, P<0.05, <0.001, respectively. Total triglyceride (TTG) level was high in the D + ALA (P<0.05) and D + COM (P<0.001) groups. In contrast, TTG level in blood of diabetes group was higher than diabetes plus antioxidant and FO administered groups (P<0.001). According to gas chromatography analysis results, while the palmitic acid raised in diabetes group (P<0.05), stearic acid in D + FO, D + ALA, and diabetes groups was lower than control (P<0.05), oleic acid reduced in D + COM and D + FO groups, but its level raised in D + AA6P and D + ALA groups (P<0.01). As the linoleic acid (LA) elevated in ALA + D, D + AA6P, and diabetes groups, linolenic acid level in diabetes, D+AA6P, and D+FO groups was lower than control (P<0.001). Arachidonic acid (AA) decreased in D + ALA, D+AA6P, and diabetes groups (P<0.01), but its level in D + COM and D + FO was higher than control (P<0.05). Docosahexaenoic acid (DHA) increased in D + AA6P and D + COM (P<0.05). While the total saturated fatty acid level raised in diabetes group, its level reduced in D + ALA and D + FO groups(P<0.05). In contrast,total unsaturated fatty acid level in D + ALA and D + FO groups was higher than control (P<0.05). In conclusion, present data have confirmed that the combination of the ALA, AA6P, and FO have improvement effects on the recycling of GSSG to reduced GSH in erythrocytes of diabetic rats, and in addition to this, oxidative stress was suppressed by ALA and AA6P, and unsaturated fatty acid degree was raised by the effects of ALA and FO.
Keywords: alpha lipoic acid; ascorbic acid-6-palmitate; fish oil; erythrocytes; lipid composition; reduced glutathione; malonaldehyde; fatty acids; diabetic male rats